Morphodynamics of sandy beaches under the influence of storm sequences: Current research status and future needs - Harshinie Karunarathna (Water Science and Engineering, 2019)
This paper reviews and discusses the current research status, trends, and future needs in the field of beach morphodynamics under the influence of storm sequences. The paper reviews how the three main research methods, field investigations, numerical modelling, and physical modelling, have been used to study beach morphodynamics during storm sequences. Available quantitative definitions of storm sequences at different sites are presented and discussed. It is shown that the definition of storm sequences is site-specific and requires knowledge of the storm climate, beach characteristics, and the temporal scale of beach recovery. Subsequently, the paper brings together currently available approaches aimed at describing the effect of storm sequences on beach erosion in a general way. The importance of storm chronology and the effects of an extreme storm within a sequence of storms are highlighted. Following that, the more poorly studied aspect of beach recovery in between storms within a sequence is discussed. Three indicators for defining beach recovery, namely the shoreline location, sediment volumes, and the beach state, are identified and compared. Finally, important research needs, including the need for detailed physical modelling, are identified.